Spiritualitas Inkarnasional Non-Heteronormatif: Studi Teologi Praktis-Empiris atas Pengalaman-pengalaman Seksual-Spiritual Para Individu Gay - Obed Reinhard Siregar (Asosiasi Teolog Indonesia, 2026)
The discourse on homosexuality in Indonesia continues to produce polarization across social and theological domains. Within Christian theology, many churches, under dogmatic authority and a singular interpretation of Scripture, maintain conservative attitudes that result in socio-theological rejection of gay persons, particularly regarding their sexual identity. This study offers a reflective theological response to such tension by giving voice to gay personsin articulating their spiritual and sexual experiences. Using a practical-empirical theological approach and a phenomenological-hermeneutical method, it presents a holistic theological reflection on the spirituality and sexuality of gay persons. The main thesis of this article is that homosexuality—materially and phenomenologically understood as the bodies and experiences of gay persons–are not merely objects of theological debate, but are instead loci of revelation and encounters with God within an incarnational horizon, which affirm the Divine presence within the human body as an authentic space for the gay individual’s spiritual experience. This study contends that human embodiment, including that of gay persons, should be recognized as a vital dimension shaping spiritual formation. Therefore, this article expands the discourse of practical-empirical theology within the context of queer spirituality in Indonesia.